Factors Affecting Job Satisfaction of Civil Engineers Working in Private Organizations in Kathmandu Valley - Mainali, Divesh; Shrestha, Hari Mohan; Pokhrel, Sudip (Kathford Journal of Engineering and Management, 2023)
The satisfaction of employees in their jobs holds a substantial influence on the overall success and effectiveness of an organization. This study is focused on evaluating the factors that directly affect the job satisfaction of civil engineers employed in private organizations in Kathmandu Valley. To gather primary data, structured questionnaires were distributed utilizing the summation job factors method. 120 questionnaires were collected and subsequently employed for detailed data analysis using SPSS 25. To ensure the reliability of the collected data, the internal consistency of the construct variables was assessed using Cronbach's alpha. All computed alpha values for the constructs surpassed the threshold of 0.8, indicating a high level of consistency. Data were analyzed using mean, standard deviation, frequency, percentage, and multiple linear regression. The findings revealed a high level of job satisfaction with a mean score of 3.4. Specifically, factors such as the role of supervisors, payment/salary, working conditions, empowerment and leadership, and relationships with co-workers played significant roles in influencing job satisfaction. However, the job itself and promotion opportunities were not identified as significant factors. The coefficient of determination (R2) was calculated to be 0.872, signifying that these independent variables collectively explain a substantial 87.2% of the variation in job satisfaction among civil engineers working in private organizations in Kathmandu Valley. In light of these findings, private organizations and relevant authorities must prioritize enhancing the core responsibilities tied directly to the job, as well as providing ample opportunities for career advancement.